Supporting unanticipated dynamic adaptation of object-oriented software - Redmond, Barry (Trinity College (Dublin, Ireland). School of Computer Science & Statistics, 2004)
Dynamic adaptation of a running program allows the program's behaviour to be changed without stopping or restarting it. Examples of the need for this are in updating long-running systems that cannot be halted and in adapting mobile systems to transient changes in their environment. While it is possible to support dynamic adaptation when it is anticipated during the system design, it is difficult, if not impossible, to anticipate all the ways in which a system may need to be dynamically adapted. One way to address this problem is to use a software architecture that supports modifications to the running program without requiring any static preparation or anticipation of the modifications in the program design or implementation. Such architectures support unanticipated dynamic adaptation.
Keywords: Computer Science, Ph.D.; Ph.D. Trinity College Dublin